MEME COMIC AS THE DEVELOPING MEDIA OF SPEAKING FOR STUDENTS IN JUNIOR HIGH SCHOOL - Muhammad Arif Sanjaya; Rahmad Husein; Maya Oktora (Universitas Negeri Medan, 2018)
This research was aimed to develop appropriate, interesting and attractive speaking media in teaching descriptive text for seventh grade students of MTsS UMMI Lubuk Pakam. Due to the result in the form of product, this study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (1989) theory with some modifications. The subject of this study was the seventh grade students of MTsS UMMI Lubuk Pakam. In conducting this research, the procedures were gathering the data and information, conducting the need analysis, designing the first draft of media, revising the media, and producing the final product as the meme comic. The instruments of collecting data were the combination of two strategies; interview and questionnaires. The interview result was analyzed as qualitative data and the questionnaires analyzed as quantitative data. These data were needs of students covering target needs and learning needs. This study developed speaking media which only focused on descriptive text taught in the odd semester. These media was based on Curriculum 2013. Keywords : Developing speaking media, seventh grade students, descriptive text, Meme Comic.